RHETORICAL STRATEGIES USED IN THE ENGLISH PERSUASIVE ESSAYS OF INDONESIAN UNIVERSITY STUDENTS OF EFL - Cahyono, Bambang Yudi (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
The purpose of this study was to investigate the use of rhetorical strategies in English persuasive essays written by Indonesian university students of English as a foreign language. This study also examined to what extent overall proficiency in English composition was predictive of the rhetorical strategies used in English persuasive essays. Two groups of undergraduate students were involved: the first- and fourth-year students in the English department of the State University of Malang, Indonesia. This study showed that that there was a statistically significant difference between the rhetorical strategies used in English persuasive essays written by the first- and fourth-year students. In general, the fourth-year students were more successful than the first-year students in using the superstructure of argument, the Toulmin model of informal reasoning, and the persuasive appeals. This study also showed that there was a positive significant correlation between the students' overall proficiency in English composition and the rhetorical strategies used in English persuasive essays.